Quality of Labor and Delivery Services: Maternal Satisfaction Study from a Tertiary Hospital - Dhakal Chalise, Gita; Shrestha, Sabina; Adhikari, Bibhav (Medical Journal of Shree Birendra Hospital, 2021)
Introduction: Maternal satisfaction is an important indicator for any hospital to measure the quality of labor and delivery services. Satisfaction with the care received during labor and childbirth process influences the decision of institutional delivery for future utilisation. This study aims to identify the satisfaction of postnatal mothers towards labor and delivery service in a selected hospital. Methods: It is a descriptive cross-sectional study. Non-probabilistic purposive sampling technique was used to select a sample. A total of 54 postnatal mothers were interviewed using a semi-structured interview schedule. It was adapted from Donabedian Model and Respectful Maternity Care (RMC) Scale focusing on four aspects i.e. health institution related aspect, interpersonal aspects of care, abuse free care and informative aspects of care in five-point Likert scales. Data were coded, entered and analyzed using Statistical Package for Social Science (SPSS) version 16 for windows. Results: In this study, 79.6% of the postnatal mothers were satisfied with the overall aspects of the labor and delivery services. The component wise results show that 94.4% were satisfied in health institution related aspects while in the interpersonal aspect, 92.6% were satisfied. Similarly, all sampled mothers were satisfied with the abuse-free care system of the health institution. In informative aspects of care, 87% were satisfied and the rest (13%) were dissatisfied. Conclusions: Although the majority of mothers were satisfied, there were dissatisfaction in regards to availability of drinking water, the behaviour of staffs and the health education provided to them. By improving these aspects, quality of service will improve and thus increase women’s satisfaction with care received.